Management of Psoriatic Arthritis in Patients With Comorbidities - Liliani, Liliani; Agustina, Agustina (International Medical Journal Corp. Ltd, 2024)
Background: The management of psoriatic arthritis (PsA) in patients with comorbidities is a complex and evolving field, as evidenced by the growing body of literature. The association between PsA, psoriasis, and cardiovascular risk factors has been highlighted in several studies, revealing the intricate interplay between systemic inflammation and comorbid conditions. Literature Review: The literature reveals a significant correlation between PsA, psoriasis, and an increased risk of cardiovascular diseases (CVD) and metabolic syndrome (MS). Chronic inflammation associated with PsA and psoriasis is a critical factor that exacerbates the risk of major adverse cardiovascular events (MACEs) and other comorbidities, including obesity, hypertension, and diabetes (Peluso et al., 2019), (Peralta et al., 2019), (Kumthekar & Ogdie, 2020). Conclusion: In conclusion, the literature underscores the necessity of a holistic approach to managing PsA in patients with comorbidities. Effective treatment must encompass both the management of psoriatic disease and the associated health risks, with careful consideration of the interactions between therapies and comorbid conditions. Future research should focus on refining treatment strategies that address these complexities to improve patient outcomes and reduce the burden of comorbidities in this population.